2015
DOI: 10.1111/1471-0528.13724
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal ultrasound cervical length for prediction of spontaneous labour at term: a systematic review and meta‐analysis

Abstract: Background The possibility to predict the delivery date is a question frequently raised by pregnant women. However, a clinician has currently little to predict when a woman at term will deliver.Objective To evaluate the predictive accuracy of transvaginal ultrasound (TVU) cervical length (CL) for spontaneous onset of labour in singleton gestation enrolled at term by a meta-analysis.Search strategy We performed a literature search in electronic databases. Selection criteriaWe included only studies assessing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…7 The DOR is defined as the ratio of the odds of the test being positive if the subject has a disease, relative to the odds of the test being positive if the subject does not have the disease, that is, LR+/LRÀ. 8 Potential publication bias was formally assessed through Egger's regression asymmetry test. Following specific indications for meta-analyses of diagnostic accuracy, we correlated individual study sample sizes with both sensitivity and specificity as measures of test accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The DOR is defined as the ratio of the odds of the test being positive if the subject has a disease, relative to the odds of the test being positive if the subject does not have the disease, that is, LR+/LRÀ. 8 Potential publication bias was formally assessed through Egger's regression asymmetry test. Following specific indications for meta-analyses of diagnostic accuracy, we correlated individual study sample sizes with both sensitivity and specificity as measures of test accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…The DOR is defined as the ratio of the odds of the test being positive if the subject has a disease, relative to the odds of the test being positive if the subject does not have the disease, that is, LR+/LR− …”
Section: Methodsmentioning
confidence: 99%
“…Few prognostic tests are available to predict PTB. Short cervical length (CL) measured by transvaginal sonography (TVS) has been shown to be a good predictor of spontaneous PTB in both singleton and twin gestations.…”
Section: Introductionmentioning
confidence: 99%
“…24 On the other hand, another recent systematic review and meta-analysis reported a moderate benefit of transvaginal ultrasound cervical length at 37–41 weeks for predicting spontaneous labor: a woman with a CL 30mm has less than a 50%, while one with a cervical length <10mm has greater than an 85%, chance of delivering within 7 days. 21 However, the pooled sensitivity in this analysis for cervical length <30mm was only 64% and pooled specificity only 60%.…”
Section: A Timeless Frustration: Cervical Evaluation Is Imprecisementioning
confidence: 62%
“…3 With respect to term spontaneous labor, a recent meta-analysis demonstrated that a woman with singleton gestation and transvaginal ultrasound cervical length of >30 mm has less than 50% chance of spontaneous labor within 7 days, while her chance is greater than 85% if her cervical length is 10 mm. 21 These are only a few of the hundreds of studies of transvaginal ultrasound cervical length for prediction of delivery timing. Fortunately, for measuring cervical length, contemporary practitioners have more than their fingers at their fingertips.…”
Section: A Timeless Approach: Evaluate Her Cervixmentioning
confidence: 99%